New Strategy for Sustainable and Equitable Economic Growth (Central and Regional Synergy) - Metekohy, Stellamaris; Sangaji, Maryam; Ramly, Fahrudin (Jurnal Ekonomi, 2024)
This writing aims to find out in depth that to increase economic growth it is necessary to provide human resources, natural resources, capital formation and investment which must continue to be stimulated and innovated to produce quality products. What is no less important is reducing disparities between the center and regions as well as structural gaps. It is necessary to realize that the limited natural resources available and human needs continue to increase, which requires more efficient use of natural resources so that future generations can still enjoy resources because the amount of available resources is the maximum limit for economic growth. In various countries the development process tends to lead to government failure, the impact of which is often more severe than market failure because it creates high transaction costs which constitute economic efficiency and hinder equality and growth. In the current development paradigm, government power must be increasingly limited to areas of managing "public good" and areas where the private sector and society have no incentive to do so. In the perspective of the concept of balance, it is required to pay attention to balance and justice between generations (intergenerational equity). The concept of a development approach known as sustainable development is a concept that meets the needs of the current generation without sacrificing future generations. The government needs to provide opportunities for the business world and society to develop while continuing to supervise in accordance with applicable regulations, so that the principles of justice can be upheld.